Pengembangan Media Audiovisual pada Materi Listrik Kelas V Menggunakan Pendekatan Saintifik - Selly Pratiwi; Dara Fitrah Dwi; Tiflatul Husna; Beta Rapita Silalahi; Dalimawati Khadir (Kappa Journal, 2026)
This study produced an audiovisual learning media based on the scientific approach for Grade V elementary school electricity material. The media was developed using a Research and Development (R&D) model with the ADDIE approach, up to the development and validation stages. Data collection instruments included teacher and student questionnaires, teacher interviews, and observations. A total of 28 Grade V elementary students participated as respondents. Validation results by material and media experts showed a very high feasibility level (83.33% and 97.33%). Analysis of teacher and student responses indicated the media's effectiveness in improving understanding and learning motivation. Further research is needed to validate the effectiveness and sustainability of this learning media in the long term.